Self-efficacy and technology usage among social service practitioners—A structural equation modeling. - Mo, Kitty Yuen-Han; Cheung, Johnson Chun-Sing; Ho, Stanley Chun-Yu; Ng, Elvis Ho-Hei (British Journal of Social Work, 2025)
This study examines the relationship between digital self-efficacy, general self-efficacy, and technology usage among social service practitioners. An online survey questionnaire was sent to social service practitioners and the results indicated a positive relationship between the three variables. In addition, general and digital self-efficacy differed according to the educational level. Moreover, digital self-efficacy has a greater effect on technology usage than general self-efficacy. Additionally, a digital self-efficacy measurement scale was validated for use in the social services sector. This study covers a wide range of social service areas and provides a comprehensive understanding of the technology usage.